Pentingnya lingkungan keluarga dalam menjaga kesehatan mental bagi remaja - Mahsuni, Intan Sukma (Maliki Interdisciplinary Journal, 2023)
In the period between childhood and adulthood known as adolescence, a child undergoes physical, behavioral and psychological changes. They begin to find their true selves and have a desire to get to know them. Mental health is a state of a person who has developed all physical, intellectual, and emotional aspects optimally and in harmony, so as to minimize the presence of emotional disorders, unacceptable behaviors or thoughts, and can interact with the surrounding environment. With so many cases afflicting adolescents now, the role of the family environment is very important to maintain mental health in adolescents. The family environment here is: parenting style to children. Harmony in the family, closeness to siblings, social and economic family and moral education to children. The family is the first and most important environment for a child. Parenting is how parents raise their children, guiding, educating, and training them to act in ways that benefit their future well-being. A good family environment is a family environment that provides provision to their children, both in the form of religious, moral, and character provisions. In addition, good parenting also affects mental health in adolescents.